HOUT-18. SAFETY OF COMMERCIAL AIRFLIGHT IN PATIENTS WITH BRAIN TUMORS – A CASE SERIES. Issue 11 (6th November 2017) - Phillips, Michelle; Saria, Marlon Garzo; Eisenberg, Amy; Kelly, Daniel; Barkhoudarian, Garni
Abstract: INTRODUCTION: Patients with intracranial masses are often advised to avoid airflight due to concerns of worsening neurological symptoms. However, many patients often travel to tertiary care neuro-oncology centers and some travel internationally. This study assesses the safety of commercial airflight for brain tumor patients without severe or progressive neurological deficits. METHODS: Patients that had traveled to our institution for surgical evaluation via commercial airflight from 2014-2017 were identified. An electronic survey was administered (RedCap) and flight duration, aircraft type, presenting symptoms and new or worsened peri-flight symptoms were queried. Severity was assessed using visual analogue scale (VAS). Significant change of symptoms was determined to be greater than 25%. Demographics and clinical history obtained from electronic medical records. Providence Health System IRB: 16-168. RESULTS: 40 patients were enrolled and completed the study. Patients had an average age of 47.7years and were 65% female. Pathology included parasellar tumors (60%), Meningiomas (20%), Metastatic tumors (5%), Gliomas (5%), Pineal tumor (5%), cerebello-pontine tumor (5%). Average flight duration: 6.5 h (range 1-17h). Average tumor volume 11.1cc and average maximal dimension 2.5cm. Nine (22.5%) patients developed worsened symptoms during airflight. These include headaches 3/19 (15.8%), fatigue 3/14 (21.4%), dizziness 3/5 (60%) and ear pain 3/3 (100%). Six patients (66.7%) had sustained worsened symptoms after airflight. Only one patient had symptoms that worsened to a severe level (transiently during flight – VAS 9/10). There were no permanent neurological deficits related to airflight. There was no correlation with tumor size, flight duration, and peri-flight corticosteroid usage. No patient with completely asymptomatic tumors developed new symptoms during flight. CONCLUSIONS: Patients with brain tumors traveling via commercial airflight can do so with acceptable symptom exacerbation. No permanent neurological deficits were noted due to air travel.